Civil Responsibility Model of Coastal State to Oil Pollution in the Sea as the Impact from the Stipulation of Dumping Area by Tanker Ship - Purwendah, Elly Kristiani; Djatmiko, Agoes; Pudyastiwi, Elisabeth (The Indonesian Journal of International Clinical Legal Education, 2019)
The research results showed that dumping is stillunderstood pluralistically in Indonesian Legal System through someexisting laws, such as Law No. 17 of 1985 on the Ratification ofUNCLOS, Law No. 32 of 2009 on Environmental Protection andManagement, the Government Regulation No. 29 of 2014 on thePrevention of Environmental Pollution, the Regulation of the Minister ofMaritime Number 136 of 2015 on the Second Amendment to theMinisterial Regulation No. 52 of 2011 on Dredging and Reclamation,and the Ministerial Decree No. 4 of 2005 on the Prevention of Pollutionfrom Ships. Dumping Countermeasures in general is still understood asan act of dredging and reclamation as the cause of the silting ofshipping channels. Indonesia has not ratified the London DumpingConvention. The list of wastes that need special arrangements and isabsolutely not disposed in the territory of the coastal states has notbeen set. Therefore, compensation has not been the priority of theprotection to the marine environment by the state. The responsibility ofthe state through the State Attorney requires procedural formalities inthe form of a special power of attorney. Hence, a cooperation withrelevant institutions, in this case the Ministry of Environment andForestry, is necessary. Currently in Indonesia, there are too manyoverlapping authorities among the agencies that resulted in opposinginterest in interpreting the issues of civil lawsuit for environmentaldamages. The model that we offerred is on putting environmentalpriorities in one ministry, which is the Ministry of Environment andForestry, through the State Attorney.